The 22 Immutable Laws of Branding : how to build a product or service into a world-class brand - Ries, Al.; Ries, Laura (New York : Collins Business, 2002)
The definitive text on branding, pairing anecdotes about some of the best brands in the world, like Rolex, Volvo, and Heineken, with the signature savvy of marketing gurus Al and Laura Ries. Claims that the only way to stand out in today's marketplace is to build your product or service into a brand--and provides the step-by-step instructions you need to do so. Tackles one of the most challenging marketing problems today: branding on the Web. The Rieses divulge the controversial and counterintuitive strategies and secrets that both small and large companies have used to establish internet brands. The 22 Immutable Laws of Branding is the essential primer on building a category-dominating, world-class brand
The 22 immutable laws of branding -- The 11 immutable laws of internet branding
"This edition combines The 22 immutable laws of branding and The 11 immutable laws of Internet branding, with added illustrations and text."
Includes index.
Keywords: Branding (Marketing); Marketing -- Decision making; Internet marketing